ANALYSIS OF PB CONTENT IN LEAVES OF COVERING PLANTS IN VARIOUS ROADS IN PALEMBANG CITY - Hasdevi Hasdevi; Suheryanto Suheryanto; Susilawati Susilawati (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Alternative Decree of the Director General of Oil and Gas No. 3674K/24/DJM/2006 dated March 17, 2006 concerning Standards and Quality (Specifications) of Gasoline-Type Fuel Oil Marketed Domestically where in the attachment to the Specification for Gasoline-Type Fuel Oil RON 91 and RON 95 (Pertamax) still contains Pb of 0.013 grams per liter. The exhaust gas produced by motorized vehicles using leaded fuel emits Pb into the environment and has the potential to be absorbed into the leaf tissue of road shade plants. The aim of this study was to examine the Pb content in the leaves and determine the effect of the Pb content in the ambient air on the Pb content in the leaves of various cover crops on Jalan Raya Palembang City. The research samples were leaves of mahogany, umbrella tree, burmese rosewood, bullet wood tree, and rain tree which were dominant and had similarities on Jl. Soekarno Hatta – Alamsyah Ratu Prawiranegara, Jl. Cabbage. H. Burlian, Jl. Jend. Sudirman, Jl. Jend. Basuki Rahmad, Jl. Jend. R. Soekanto, Jl. Jend. Ahmad Yani. Jl. governor HA. Bastari. Analysis of the Pb content in leaves and air using the AAS (Atomic Absorption Spectrophotometer) method. The results of the study found that the highest Pb content in the leaves of the Mahogany plant was on Jl. Jend. Basuki Rahmad 0.112 mg/kg while the lowest was on Jl. governor HA. Bastari <0.081 mg/kg. Pb content in umbrella tree plants in all roads < 0.081 mg/kg. The highest Pb content in burmese rosewood plants is on Jl. Jend. Basuki Rahmad 0.116 mg/kg while the lowest was on Jl. governor HA. Bastari <0.081 mg/kg. The highest Pb content in bullet wood tree Jl. Jend. Basuki Rahmad 0.099 mg/kg while the lowest is on Jl. governor HA. Bastari <0.081 mg/kg. The highest Pb content in rain tree is on Jl. Jend. Basuki Rahmad 0.089 mg/kg while the lowest is on Jl. governor HA. Bastari <0.081 mg/kg. The highest Pb content in ambient air is on Jl. Jend. Basuki Rahmad 0.06 ʯg/Nm3 while the lowest is on Jl. Jend. R. Soekarno. The Pb content in the ambient air affects the Pb content in the leaves.